2010
DOI: 10.1007/s11657-010-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamins K1, K2 and bone mineral density: the Hordaland Health Study

Abstract: Associations between bone mineral density (BMD) and dietary vitamins K1 and K2 in 4,461 individuals were studied. For women, odds ratio of low BMD was 1.48 in lowest to highest quartile of K1. A weak positive association was found for K2. Our results do not support dietary vitamins K as being major determinants of BMD.Purpose Some studies suggest a positive association between intake of vitamin K1 (phylloquinone) or vitamin K2 (menaquinone) and BMD. The objective was to examine associations between BMD and die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…However, even though the documentations of similar effects of vitamin K 1 is not as strong as K 2 , a combination of low serum levels of vitamins K 1 and D have been associated with increased risk of hip fracture in elderly [ 37 ]. Both low levels and intakes of vitamin K 1 have been associated with osteoporosis [ 19 22 ], and our findings indicate that vitamin K 1 has a positive effect as well.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, even though the documentations of similar effects of vitamin K 1 is not as strong as K 2 , a combination of low serum levels of vitamins K 1 and D have been associated with increased risk of hip fracture in elderly [ 37 ]. Both low levels and intakes of vitamin K 1 have been associated with osteoporosis [ 19 22 ], and our findings indicate that vitamin K 1 has a positive effect as well.…”
Section: Discussionsupporting
confidence: 62%
“…In humans, the fraction of the circulating osteocalcin that is not γ-carboxylated (GLU/GLA) is used as a biomarker of vitamin K status [ 17 , 18 ]. Low levels of vitamin K 1 and K 2 has been observed in osteoporotic patients [ 19 , 20 ], and low dietary intake of vitamin K 1 has been associated with low bone mineral density (BMD) and increased risk of hip fracture [ 21 , 22 ]. Furthermore, it is shown that undercarboxylated osteocalcin increases with age [ 23 ], and high levels are associated with both lower BMD and increased risk of hip fracture [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, two Japanese studies showed that the usual dietary intake of natto was effective in maintaining bone stiffness ( 97 ) and was positively associated with a 3-year change in BMD at the femoral neck ( 98 ) . Within Norwegian individuals, no linear association was found between dietary menaquinones and BMD of the total hip; however, fractional polynomial regression analyses for the detection of non-linear associations showed a small, positive association between dietary menaquinones and BMD among women ( 99 ) . Of note, these studies described a proposed effect of dietary menaquinones via natto consumption.…”
Section: The Amount Of Menaquinones Required To Prevent Chronic Diseasesmentioning
confidence: 94%
“…Described in Apalset et al. (): (Koivu‐Tikkanen et al., ; Schurgers and Vermeer, ); Finnish food composition database (National Institute for Health and Welfare, )…”
Section: Appendix G – Estimated Dietary Intakes Of Phylloquinone and ...mentioning
confidence: 99%